Comparative analyses of arthroscopic and open repairs of lateral ligament complex injuries of the ankle: a systematic review and meta-analysis of the medium-term outcomes - Tonsuthanluck, Sora; Handoyo, Henry Ricardo; Tharincharoen, Ramita; Angthong, Chayanin (My University, 2024)
Purpose: Little is known regarding the comparative analyses of the medium-term outcomes (with a mean minimum follow-up period of 24 months), between arthroscopic and open repairs of lateral ligament complex (LLC) injuries of the ankle. Thus, in this study, we aimed to explore the comparative analyses regarding the medium-term follow-up outcomes of these repairs, by conducting a systematic review and meta-analysis. Methods: The systematic review and meta-analysis were performed as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines; data were extracted from the PubMed and Google Scholar databases. From an initial search, a total of 1182 abstracts (280 and 902 abstracts, from PubMed and Google Scholar, respectively) were found and screened in accordance with the eligibility criteria. Subsequently, six articles were found to be eligible for further review. Results: A total of 419 patients underwent surgical repairs; 205 and 214 patients underwent arthroscopic and open repairs, respectively. The mean minimum follow-up period was 29.2 months. The medium-term follow-up for arthroscopic LLC repairs was found to be superior to that of open LLC repairs, with more favorable outcomes; as evidenced by better clinical scores, lower pooled complication rates, earlier return times to pre-injury sport, and higher early sport ratios. Conclusions: The findings of this systematic review and meta-analysis support near-future developments validating arthroscopic repair as the new gold standard for LLC repairs, similarly to arthroscopic ligament and tendon repairs, as well as arthroscopic reconstruction surgeries, of the knee and shoulder.
Keywords: Ankle instability; Arthroscopy; Chronic ankle sprain; Lateral ligament complex repair; Open modified Broström–Gould procedure